Constant hydraulic supply and ABA dynamics facilitate the trade-offs in water and carbon - Abdalla, Mohanned; Schweiger, Andreas H.; Berauer, Bernd J.; McAdam, Scott A. M.; Ahmed, Mutez Ali (Frontiers in Plant Science, 2023)
Carbon-water trade-offs in plants are adjusted through stomatal regulation. Stomatal opening enables carbon uptake and plant growth, whereas plants circumvent drought by closing stomata. The specific effects of leaf position and age on stomatal behavior remain largely unknown, especially under edaphic and atmospheric drought. Here, we compared stomatal conductance (gs) across the canopy of tomato during soil drying. We measured gas exchange, foliage ABA level and soil-plant hydraulics under increasing vapor pressure deficit (VPD). Our results indicate a strong effect of canopy position on stomatal behavior, especially under hydrated soil conditions and relatively low VPD. In wet soil (soil water potential > -50 kPa), upper canopy leaves had the highest gs (0.727 ± 0.154 mol m-2 s-1) and assimilation rate (A; 23.4 ± 3.9 µmol m-2 s-1) compared to the leaves at a medium height of the canopy (gs: 0.159 ± 0.060 mol m2 s-1; A: 15.9 ± 3.8 µmol m-2 s-1). Under increasing VPD (from 1.8 to 2.6 kPa), gs, A and transpiration were initially impacted by leaf position rather than leaf age. However, under high VPD (2.6 kPa), age effect outweighed position effect. The soil-leaf hydraulic conductance was similar in all leaves. Foliage ABA levels increased with rising VPD in mature leaves at medium height (217.56 ± 85 ng g-1 FW) compared to upper canopy leaves (85.36 ± 34 ng g-1 FW). Under soil drought (< -50 kPa), stomata closed in all leaves resulting in no differences in gs across the canopy. We conclude that constant hydraulic supply and ABA dynamics facilitate preferential stomatal behavior and carbon-water trade-offs across the canopy. These findings are fundamental in understanding variations within the canopy, which helps in engineering future crops, especially in the face of climate change.